Accuracy of GRK-2200T Auto-refkeratometer in Subjective Acceptance for Refractive Errors - Adhikari, Bishwa Nath; Gautam, Pramod Sharma; Upadhyay, Shishu; Prakash, Uday Chandra (Birat Journal of Health Sciences, 2019)
Introduction: Globally, the most common cause for diminution of vision is refractive errors and the number of patients with refractive errors is increasing day by day. The Auto-refraction (AR) is quick and patient friendly procedure as compared to retinoscopy and subjective refraction in finding out refractive errors. Hence, the accuracy of Auto-refractometer in terms of subjective acceptance (SA) should be taken into account before prescribing optical correction based on findings of that particular model of Auto-refractometer. So, this study is directed towards analysis of the accuracy of GRK-2200T Auto-retieratometer in terms of acceptance by comparing findings of AR with that of SC. Objectives: The aim of this study was to assess the refractive status of patient's eyes using auto refractometer (GRK-2200T auto-retierato meter) and to estimate the agreement of it in terms of accuracy in acceptance of subjective correction by the patient. Methodology: A hospital based prospective comparative study conducted on 226 eyes of 113 patients who visited out-patient department (OPD) of Ophthalmology at Nobel Medical College and Teaching Hospital (NoMCTH), Biratnagar diagnosed with Myopia, Hyperopia and Astigmatism. Duration of study was 4 months from 2nd October, 2018 to 2nd February, 2019. All data thus collected was subjected to statistical analysis by using SPSS version 22. Result The mean age of the study subjects was 26.91±7.79 years with male to female ratio of 0.47. When spherical power, cylindrical power and the axis are taken into consideration together, only 13.3% of the total tested eyes subjectively accepted the AR values unchanged. On subjective correction, 32.7% of the tested eyes accepted spherical power while 46.5% accepted cylindrical power and 50.9% accepted axis of AR unchanged. About 52.2% of the total eyes examined fall within the deviation of spherical equivalent (SE) of ±o.25D and up to 67.3% of them fall within the deviation of ±o.50D. Conclusion The auto refraction by GRK-2200T auto-retieratometer was found to be satisfactory for a preliminary refraction but not satisfactory as substitutes for conventional subjective refraction. However, auto refraction values obtained by GRK-2200T auto-retieratometer could be important in order to accurately prescribe the cylindrical power as well as its axis than the spherical component.